Unlocking the enterpriser inside! : a book of why, what and how! - Vyakarnam, Shailendra; Hartman, Neal (World Scientific, 2011)
"This book is based on a highly successful joint project between the University of Cambridge and the Massachusetts Institute of Technology (MIT), under the auspices of the Cambridge-MIT Institute. The project brings together communities of highly diverse individuals to share and learn how to be enterprising. It has run 17 times with the positive outcomes of not only training more enterprising individuals, but also building capacity in universities. The unique feature of this book is how it covers learning in enterprising skills, while at the same time builds capacity in such a way that the alumni themselves can take what they have learned for the benefit of others. Through this book, the authors intend to share what they have learnt and to transmit their passion for this program to others for personal development. Hopefully, others will then repeat this positive experience and make a difference to their respective institutions and communities"--Book jacket